Analysis of travel-to-work characteristics : a case study of industrial workers in the northern corridor, Bangkok - Anuradha, Kamath; Nakamura, Fumihiko; Kammeier, Hans Detlef; Archer, R. W.; NORAD (Norwegian Agency for International Development Assistance) (Bangkok : Asian Institute of Technology, 1994)
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
The Northern Coll'idor forms one of the busiest corridors in Thailand, radiating from Bangkok and connecting the northern pa1t of Thailand. It has been experiencing rapid industrial development in the past few decades, leading to increased travel demands especially for the indust1ial workers. The principal thesis of this study is that the journey-to-work presents the most serious transportation problem in the Northern Coll'idor. It is mainly concerned with attempting to define the travel-to-work characteristics of industrial workers by analyzing their socio economic and travel characteristics. The socio economic analysis revealed that most of the workers were women, and the distance commuted daily, depended on the age, sex and income of the workers. Traffic congestion and long detour routes were the main transportation problems perceived. In the past few years there has been a noticeable shift in the choice of transport mode used in the journey-to-work by the industrial workers. It is seen that the workers now prefer to travel by private vehicles, rather than use the public buses or trains. Application of the Regression Model showed that, private vehicles contributed significantly to the total ttips generated by industries. The application of the Binary Logit Model concluded that the predicted modal split of the public bus was higher than that of the private vehicles and bike taxi. The predicted modal split of the song teaw was almost balanced with that of public bus for short distances but decreased significantly with increase in distance. The results of the Generalized Cost Model showed that, the low income workers had less modal choice, especially for long distances as compared to middle and high income workers. The private motorbike proved to be a common mode for the middle income workers and the private car a primary mode for the high income workers. The Detour Distances analyzed was based on the 'U' turn facilities in the present situation, the proposal by the Dept. of Highways and a new proposal by the researcher. The results revealed that the proposal by the Dept. of Highways had the maximum detour distance and the maximum generalized cost leading to a disbenefit in terms of total generalized cost per trip per day as compared to the present situation. The new proposal by the researcher showed least detour distance, least generalized cost and a benefit in total generalized cost per trip per day as compared to the present situation. Based on the above analysis certain policies are recommended to influence the modal split by altering the pricing and investment policies in order to achieve the most efficient and economical (in cost - benefit terms) balance between public and private transport.
Thesis (M.Sc.) - Asian Institute of Technology, 1994
Keywords: Travel -- Research -- Thailand -- Bangkok